RADIATION THERAPY OF MENINGEAL HEMANGIOPERICYTOMAS (LITERATURE REVIEW AND CLINICAL OBSERVATION) - A. V. Nazarenko; T. N. Borisova; S. V. Medvedev; D. S. Romanov; Yu. A. Gerasimov; A. Kh. Bekyashev; A. A. Mitrofanov; G. E. Gorlachev; V. A. Boldyreva (Опухоли головы и шеи)
Meningeal hemangiopericytomas are rare tumors of the meninges developing from pericytes. The main method of their treatment is surgery aimed at total removal of the tumor. Analysis of the literature studies shows high potential of post-operative distant radiation therapy to increase duration of relapse-free survival of these patients. The recommended total radiation dose varies from 50 to 60 Gy (and in some publications, it exceeds 60 Gy). Radiation is applied as classic fractionation and hypofractionation, and different types of radiosurgery and stereotaxic radiotherapy are suitable approaches to treatment of recurrent meningeal hemangiopericytomas in patients with a history of radiation therapy.